Addressing The Challenges of The Times Through The Concept of Character Education By Ki Hajar Dewantara - Wijayanti, Tutik; Irawan, Hendri; Nugroho, Dedy Ari; Utama, Nanda Julian (IJORER : International Journal of Recent Educational Research, 2025)
Objective:The importance of developing strong character and good morals in individuals in facing the challenges and changes brought about by digital technology. The importance of character education in equipping learners with the concept of Ki Hajar Dewantara in the holistic and sustainable independent curriculum. Method: This research utilizes a qualitative descriptive approach by conducting literature and case studies in schools. Data were collected through observations, interviews, and documents related to the curriculum and implementation of character education. Results: of the study indicate that the education transformation adopting the concept of Ki Hajar Dewantara in the independent curriculum has a positive impact on students' character development. Concepts of character education such as cooperation, independence, love for the homeland, and diversity are well integrated into learning practices. Through this approach, students become more active, motivated, and capable of developing positive attitudes, moral values, and social skills. Novelty: The research identifies several challenges in applying Ki Hajar Dewantara’s concept within the independent curriculum, including curriculum alignment with student needs, teachers’ readiness, and the required support from schools and stakeholders. The study finds that this concept has strong potential to nurture excellent character in the independent curriculum. Its novelty lies in presenting a clear integrative analysis that connects Ki Hajar Dewantara’s philosophical principles with the operational framework of the independent curriculum an approach not explicitly formulated in previous studies. This contribution enhances understanding of character education’s role in holistic and sustainable educational transformation.